DENTAL CARIES, THE LEVELS OF FLOUR WATER WELLS AND THE GEOGRAPHICAL CONDITIONS IN DISTRICT COMMUNITY ASEMBAGUS SITUBONDO BASED ON GOOGLE EARTH - , Hestieyonini Hadnyanawati ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Asembagus is a sub district (Kecamatan) in Situbondo, East Java province. Geographically location of Situbondo is situated south of the Madura Strait. Sub Asembagus borders the sea, the majority of its people consume drinking water comes from water wells. Well water in the vicinity of the sea to get water supply from groundwater itself or from the absorption sea water flow containing high fluorine minerals so much more. Fluorine in drinking water consumption influences the State of the enamel of teeth, if in very small amounts could hinder the process of demineralization (the formation of dental caries), while large quantities cause fluorosis. This research aims to find out view of the levels of Fluorine, and dental caries based on geographical location. Types of observational research descriptive with cross sectional approach. The results showed that the average levels of fluorine water wells is 3.58, an average of dental caries of the population is O.The Data displayed in the form of tables and to geographically separate conditions as well as its geographical location using Google earth.